Effect of net shading technology on the yield quality and quantity of chilli pepper under greenhouse cultivation - Agyemang Duah, Stella (Acta Agraria Debreceniensis, 2021)
This study was undertaken to identify the effect of net shading technology on the total capsaicinoids, vitamin C and relative chlorophyll content expressed as SPAD (Soil Plant Analysis Development) values and total marketable fruit yield of ‘Star Flame’ chilli pepper (Capsicum annuum) for two harvesting times cultivated under modified atmosphere. ‘Star Flame’ pepper was grown under three (3) different net shading colours (white, red and green). Samples without net shading were used as control. Samples were subjected to chromatographic analyses using HPLC for the determination of total capsaicinoids and vitamin C. Interaction in shading technology and harvest times (p=0.010) had significant effect on total capsaicinoids as a result of green and white shading technologies showing higher differences when compared to control samples. Vitamin C content was observed to have increased in white and red shadings (p=0.001) after the first harvest and gradually decreased after the second harvesting time (p=0.002). Relative leaf chlorophyll content was significantly higher in white shading in the first and second harvest. Samples used as control had significantly higher marketable values when compared to white and green shadings with red recording low marketability of ‘Star Flame’ chilli peppers.